The 'Modernisation' of Scotland and its Impact on Glasgow, 1955–1979: 'Unwanted Side Effects' and Vulnerabilities. Issue 3 (August 2016) - Collins, Chik; Levitt, Ian
Abstract : This article reports findings of research into the far-reaching plan to 'modernise' the Scottish economy, which emerged from the mid-late 1950s and was formally adopted by government in the early 1960s. It shows the growing awareness amongst policy-makers from the mid-1960s as to the profoundly deleterious effects the implementation of the plan was having on Glasgow. By 1971 these effects were understood to be substantial with likely severe consequences for the future. Nonetheless, there was no proportionate adjustment to the regional policy which was creating these understood 'unwanted' outcomes, even when such was proposed by the Secretary of State for Scotland. After presenting these findings, the paper offers some consideration as to their relevance to the task of accounting for Glasgow's 'excess mortality'. It is suggested that regional policy can be seen to have contributed to the accumulation of 'vulnerabilities', particularly in Glasgow but also more widely in Scotland, during the 1960s and 1970s, and that the impact of the post-1979 UK government policy agenda on these vulnerabilities is likely to have been salient in the increase in 'excess mortality' evident in subsequent years.